Optimization of Assik Website Services (Arek Suroboyo Siap Kerjo) in Expanding Employment Opportunities in Surabaya - Zahwa Dalya Rufianty; Nurjanti Takarini (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Unemployment remains a major issue in Surabaya, despite a decline in the Open Unemployment Rate (TPT) over the past three years. This program aims to assist job seekers through direct mentoring and career counseling using the ASSIK Website (Arek Suroboyo Siap Kerjo). The methods include observation, guidance on CV and cover letter writing, and teaching how to utilize ASSIK. Assistance is routinely provided at the Surabaya City Department of Industry and Manpower, involving an average of 30 daily visitors. The study results indicate that 28 job seekers were satisfied with the services, gained an understanding of how to use the digital platform, and improved their readiness for the job selection process. Job placements managed by the Surabaya City Department of Industry and Manpower using the ASSIK Website showed a significant 30% increase compared to the previous year. Challenges include limiteds service capacity and the need to enhance ASSIK features. Recommendations include implementing an efficient queuing system and offering virtual mentoring services to reach more job seekers. Pengangguran tetap menjadi isu utama di Kota Surabaya meskipun telah menjadi penurunan Tingkat Pengangguran Terbuka (TPT) dalam tiga tahun terakhir. Program ini bertujuan mendukung pencari kerja dengan memanfaatkan Website ASSIK (Arek Suroboyo Siap Kerjo) melalui pendampingan langsung dan konseling karir. Metode yang digunakan mencakup observasi, bimbingan penyusunan CV dan surat lamaran, serta bimbingan cara menggunakan Website ASSIk. Pendampingan dilakukan secara rutin di Dinas Perindustrian dan Tenaga Kerja Kota Surabaya dengan melibatkan 30 pengunjung harian. Hasil dari penelitian, 28 pencari kerja merasa puas dengan layanan, pemahaman cara menggunakan platform digital dan kesiapan menghadpi proses seleksi kerja. Penempatan kerja yang dikelola Dinas Perindustrian dan Tenaga Kerja Kota Surabaya melalui penggunaan Website ASSIK menunjukkan peningkatan signifikan sebesar 30% dibanding tahun sebelumnya. Namun, tantangan yang dihadapi meliputi keterbatasan kapasitas layanan dan kebutuhan pengembangan fitur ASSIK. Disarankan untuk mengimplementasi sistem antrian lebih efisien dan menyediakan layanan pendampingan virtual untuk menjangkau lebih banyak pencari kerja.